2003
DOI: 10.1093/jnci/djg039
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 8 Infection and Transfusion History in Children With Sickle-Cell Disease in Uganda

Abstract: Our study suggests that blood transfusion is associated with a small risk of HHV-8 transmission. In Uganda, this risk is approximately equivalent to the 1-year cumulative risk of infection from community sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 39 publications
2
47
0
Order By: Relevance
“…Among men, HHV-8 seropositivity was signifi cantly associated with dental treatment, which may be a marker for transmission through saliva-or blood-contaminated dental instruments. Our HHV-8 associations with a history of >10 lifetime injections, tattoos, and HCV seropositivity also point to possible blood-borne transmission and agree with other studies (10,27,28). Sexual transmission might be suggested by our HHV-8 association with marital status, but this association did not persist after adjustment for age.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among men, HHV-8 seropositivity was signifi cantly associated with dental treatment, which may be a marker for transmission through saliva-or blood-contaminated dental instruments. Our HHV-8 associations with a history of >10 lifetime injections, tattoos, and HCV seropositivity also point to possible blood-borne transmission and agree with other studies (10,27,28). Sexual transmission might be suggested by our HHV-8 association with marital status, but this association did not persist after adjustment for age.…”
Section: Discussionsupporting
confidence: 90%
“…Because no standard for testing for HHV-8 infection exists, we previously based cutoff values for defi ning seropositivity on visual inspection of the distribution of the K8.1 assay optical density (OD) values (10), assuming that there are seronegative and seropositive subpopulations. However, this approach is subjective.…”
Section: Methodsmentioning
confidence: 99%
“…A study among Mulago Hospital SS patients in 2002 with regards to transfusion history using validated chart abstracts and review of the hospital record found a correlation between the caretakers' history and the hospital records 26 .…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…[4][5][6][7][8][9] However, only a few studies have investigated risk factors for progression to KS among individuals coinfected with HIV and HHV-8.…”
mentioning
confidence: 99%
“…[1][2][3] Previous studies of acquired immunodeficiency syndrome (AIDS) patients have identified risk factors for infection with HHV-8, including sexual activity among homosexual men, intravenous drug use and blood transfusion. [4][5][6][7][8][9] However, only a few studies have investigated risk factors for progression to KS among individuals coinfected with HIV and HHV-8.…”
mentioning
confidence: 99%